Improving Low Carbon Development Performance at the Local Level through Multi Criteria Decision Analysis - Fariz Basyiruddin; Arief Rachmansyah; Bunga Hidayati; Reny Tiarantika; Naziatul Aziah Mohd Radzi (Universitas Diponegoro, 2026)
Climate change necessitates immediate local interventions to guarantee environmental stability. Notwithstanding emission target agreements, Mojokerto Regency’s contribution to regional low-carbon development is less than 1%, indicating minimal influence. This study examines the enabling and constraining factors of low-carbon performance and establishes strategic priorities using the Analytical Hierarchy Process (AHP), corroborated through a Cost-Effectiveness Analysis (CEA). Data were gathered through expert interviews, pairwise questionnaires, and a regional fiscal analysis. The findings demonstrate that structural limitations, such as constrained resources and data deficiencies, impede implementation, whereas multi-stakeholder interaction serves as a key facilitator. AHP designated Community Engagement as the key choice criterion (31.32%). Thus, waste management using TPS3R was prioritized at 26.12%, followed by tree planting at 20.09% and organic fertilizer at 13.88%, together comprising 60.09% of choice preferences. CEA validates these findings, indicating that prioritized community-based methods provide enhanced fiscal efficiency, substantial landfill cost savings, and local job creation. They surpass capital-intensive alternatives, such as Intelligent Transportation Systems (ITS/ATCS), which provide minimal carbon value. This report advocates for the reallocation of municipal finance to prioritize community empowerment and nature-based initiatives, underpinned by institutional legislation that requires data sharing for Measurement, Reporting, and Verification (MRV) systems to facilitate an economically sound and socially equitable shift